World Health Organization’s Well-Being Index – WHO-5: Psychometric Performance of the Portuguese Version for Adolescents - Paula Saraiva Carvalho; Miguel Vieira Martins; Isabel Azevedo; Ricardo Rodrigues; Sofia Ferreira (Portuguese Journal of Public Health)
Introduction: The World Health Organization’s Well-Being Index (WHO-5) is a five-item scale designed to measure psychological well-being and is considered effective in detecting depressive symptoms. This scale was translated and validated in more than 30 languages and is used in clinical practice and research worldwide. In Portugal, validation of this scale has yet to be done. This study aimed to analyse the psychometric performance of the WHO-5 scale in the setting of a Portuguese adolescent population. Methods: An observational cross-sectional survey-based study was carried out to assess the emotional state of adolescents resorting to the WHO-5 scale. A sample of 1,916 elementary and secondary school students from grades 7–12 was used. Results: The WHO-5 median score was 17 [14–20], and the best scores were found in males (p < 0.001), in those with no health issues (p < 0.001), those who slept well (p < 0.001), those who practiced sports (p < 0.001), and those who had no difficulties making friends (p < 0.001). Results from the answers to the WHO-5 questionnaire showed good internal consistency with a Cronbach alpha value of 0.80, and a confirmatory factor analysis supported the unidimensional structure of the questionnaire, which was consistent with a valid scale for the study sample. Conclusion: This study showed that the Portuguese version of the WHO-5 can assess psychological well-being in adolescents. The WHO-5 is a simple and readily useable scale that can be applied in routine consultations for screening the emotional state of adolescents and early detection of signs of mental health problems.